HSP70-eIF4G interaction promotes protein synthesis and cell proliferation in hepatocellular carcinoma - Wang, Meng; Wei, Kai; Qian, Baifeng; Feiler, Svenja; Murtha-Lemekhova, Anastasia; Büchler, Markus W.; Hoffmann, Katrin (Cancers, 2020)
Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related death worldwide and features various tumor escape mechanisms from treatment-induced stress. HSP70 plays a critical role in cell protection under stress. eIF4G physiologically regulates the formation of the protein-ribosomal complex and maintains cellular protein synthesis. However, the precise cooperation of both in HCC remains poorly understood. In this study, we demonstrate that HSP70 expression is positively correlated with eIF4G in tumor specimens from 25 HCC patients, in contrast to the adjacent non-tumorous tissues, and that both influence the survival of HCC patients. Mechanistically, this study indicates that HSP70 and eIF4G interact with each other in vitro. We further show that the HSP70–eIF4G interaction contributes to promoting cellular protein synthesis, enhancing cell proliferation, and inhibiting cell apoptosis. Collectively, this study reveals the pivotal role of HSP70–eIF4G interaction as an escape mechanism in HCC. Therefore, modulation of the HSP70–eIF4G interaction might be a potential novel therapeutic target of HCC treatment.
Gesehen am 12.11.2020